Dinner church : Building bridges by breaking bread - Fosner, Verlon (Franklin, Tennessee : Seedbed Publishing, 2017)
"Christianity is the greatest rescue project the world has ever seen, yet many churches across America are shrinking instead of growing. After spending 18 years as a pastor in highly secularized Seattle, Verlon Fosner began to realize that the church had a sociological problem. While outreach efforts to find new wine were genuine, the church's old wineskin was brittle and leaking. In other words, the traditional ways of doing church were not capable of housing a new wine that would be necessary to compel a secular culture to Jesus. Somewhere in this struggle, Fosner and his leadership team began to consider the way church as done during the first three centuries, and the sociological implications of doing church around dinner tables. Inviting someone to a dinner with Jesus is a very different thing that inviting them to a worship/teaching event on a Sunday morning at a religious campus. In Dinner Church: Building Bridges by Breaking Bread, Verlon Fosner unveils how the ancient dinner church was rebirth in his Seattle community and how that vision changed his congregation forever. These pages also offer a compelling case for why many churches would do well to pause and see the pockets of lost people within the shadow of their steeples, and consider how a Jesus dinner table might open up a door to heaven for those neighbors. Revelation 3:20 makes it clear that Jesus still wants to have dinner with sinners. That likely means he wants his church to set the table."--Publisher.
1. The day we realized we had cancer -- 2. The first dinner church -- 3. Rebirth -- 4. Preaching to sinners -- 5. The healer -- 6. The message of food -- 7. Table talk and natural evangelism -- 8. A different path of salvation -- 9. Protecting new vision -- 10. Sore neighborhoods -- 11. The thing about money -- 12. Calling all church planters -- 13. The family rescue business.
"A fresh expressions book"--Cover.
Includes bibliographical references (pages 175-182).
Keywords: Evangelistic work -- United States; Church development, New -- United States; Food -- Religious aspects -- Christianity; Dinners and dining -- Religious aspects -- Christianity; Hospitality -- Religious aspects -- Christianity; Church growth